Integrating Critical Thinking into EFL Speaking Instruction: A Qualitative Case Study in Indonesian Higher Education - Gunawan Gunawan; Sahril Nur; Amirullah Abduh; Samtidar Samtidar (PT. Global Research Collaboration, 2026)
This study examines how critical thinking is integrated into EFL speaking instruction in higher education. A qualitative design was employed to gain an in-depth understanding of lecturers' critical thinking and speaking instruction. The study was conducted at Muhammadiyah University of Bone and involved 4 lecturers and 14 students. Data were collected through semi-structured interviews, classroom observations, and document analysis of lesson plans. The data were analyzed inductively using thematic analysis to identify recurring patterns in lecturers’ perceptions and instructional strategies. The analysis focused on three interconnected stages of instruction: planning, action, and evaluation. The findings reveal that lecturers perceive critical thinking in speaking as the ability to analyze issues, justify opinions with evidence, and respond thoughtfully to counterarguments. Students’ classroom participation also showed that critical thinking emerged through their ability to ask questions, compare viewpoints, justify opinions with evidence, respond to counterarguments, and reflect on the quality of their oral performance. They believe that students' speaking skills should be evaluated not only on fluency, pronunciation, and grammatical accuracy but also on their capacity to analyze issues, build logical arguments, use evidence, engage with differing viewpoints, and reflect critically on ideas.